How Storytelling and Digital Content Quality Influence Consumer Loyalty Through Customer Engagement: A PLS-SEM Study of Somethinc Skincare Consumers - Raeny Dwi Santy; Fatmawati A. Rahman; Rostini; Annisa Zhalila Razak; Rince Tambunan; Ummy Kalsum (Global Research Collaboration, 2026)
This study examines how storytelling and digital content quality shape consumer loyalty through customer engagement in the skincare industry. A quantitative explanatory design was employed using a cross-sectional survey of 120 consumers selected through purposive sampling. Eligible respondents had purchased and used the focal skincare brand and had been exposed to its official social media content. Data were collected using a 24-item questionnaire and analyzed through partial least squares structural equation modeling to evaluate the measurement model, direct relationships, and mediating effects. The results demonstrate that storytelling positively influences customer engagement and consumer loyalty. Digital content quality also has positive effects on customer engagement and consumer loyalty, while customer engagement significantly enhances consumer loyalty. The mediation analysis further shows that customer engagement partially mediates the effects of both storytelling and digital content quality on consumer loyalty. The variance accounted for values of 27.46 percent and 34.57 percent indicate complementary partial mediation for storytelling and digital content quality, respectively. Digital content quality emerges as the stronger predictor of customer engagement, suggesting that consumers respond particularly favorably to digital content that is relevant, informative, consistent, and professionally presented. The findings demonstrate that consumer loyalty is developed not only through direct exposure to compelling narratives and high-quality content, but also through the cognitive, emotional, and behavioral engagement generated by these communication strategies. This study contributes to digital marketing literature by clarifying customer engagement as a relational mechanism through which storytelling and digital content quality translate into consumer loyalty. Skincare brands should therefore integrate compelling narratives with credible and high-quality social media content to strengthen engagement and sustain long-term consumer relationships.